PLLA fiber capable of being chemically recycled and high in crystallinity and preparation method of PLLA fiber

By combining the bio-based naphthalene calcium carbonate with PLLA masterbatch and regulating its structure, the problem of poor thermal stability of PLA fibers is solved, and the preparation of PLLA fibers with high crystallinity and excellent mechanical strength is achieved. It is suitable for environmentally friendly fibers and Textile and clothing field.

CN119465434AActive Publication Date: 2025-02-18QINGDAO UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411435858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The low melting point, poor thermal stability and low crystallinity of PLA fibers limit their application in environmentally friendly fibers and textile and clothing fields.

Method used

By compounding bio-based calcium carbonate with PLLA masterbatch, and by regulating the morphological size and surface physicochemical structure of calcium carbonate in nacre, it enhances its entanglement with the PLLA molecular chain, and improves the nucleation site of PLLA. This improves the strength of PLLA melt, promotes crystallinity and improves thermal stability.

Benefits of technology

The preparation of PLLA fibers with high crystallinity has been achieved, which improves its mechanical strength and thermal stability, solves the problem of poor thermal stability of PLA fibers, and is suitable for environmentally friendly fibers and textile and clothing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465434A_ABST
    Figure CN119465434A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bio-based fiber materials, and provides a chemically recyclable PLLA fiber with high crystallinity and a preparation method thereof.The preparation method comprises the steps that bio-based pearl layer calcium carbonate extracted from common mussels is treated with a silane coupling agent and then evenly mixed with PLLA master batches according to different mass ratios, granulation is conducted again, and calcium carbonate modified PLLA composite master batches are obtained; the composite master batch is subjected to vacuum drying and then extruded from a spinneret plate of a melt spinning machine, PLLA nascent fibers are obtained, the PLLA nascent fibers are subjected to drafting and heat treatment, and the high-crystallinity PLLA fibers are obtained. The PLLA fiber prepared by the method has the advantages of high crystallinity, good thermal stability, biodegradability and chemical cycle performance. The fabric can be used in textile, clothing and medical fields. The problems that a conventional chemical fiber material cannot be degraded and is harmful to the environment are solved, and meanwhile the problems that a conventional polylactic acid material is low in crystallinity, poor in thermal stability and strength and recyclable are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bio-based fiber materials, and in particular to a PLLA fiber that can be chemically recycled and has high crystallinity, and a preparation method thereof. Background Art

[0002] With the global shortage of petrochemical resources and the increasing threat of "white pollution" to the environment, petroleum-based fiber materials represented by polyester fibers are facing the dilemma of increasingly reduced raw material sources. In the context of countries around the world actively promoting the implementation of mandatory laws and regulations such as plastic restrictions and bans, it is imperative to focus on the development and use of biodegradable and environmentally friendly materials. Polylactic acid (PLA) fiber, as a fiber material with a wide source of raw materials, renewable, biodegradable and biocompatible, is widely favored by governments and major corporate groups. PLA fiber, as a new material that is expected to alleviate resource crises and environmental pollution, is an important part of my country's new strategic materials field and an important support for building a fiber power.

[0003] Since American polymer chemist Carothers synthesized polylactic acid in an organic solvent and vacuum state in 1932, polylactic acid has been widely studied as a structural material. In 1954, DuPont used a two-step method to prepare high molecular weight polylactic acid, laying the foundation for the preparation of PLA fibers. In the late 1990s, Cargill Dow, funded by Cargill and Dow Chemical, used corn as raw material to improve the production process of industrialized production of polylactic acid, and pioneered the industrialization stage of polylactic acid. As early as 1994, Japan's Kanebo Company used melt spinning technology to produce polylactic acid fibers with the trade name "Lactron". In 2005, NatureWorks of the United States announced the independent development of lactic acid and polylactic acid comprehensive business. The scale of polylactic acid production equipment is the largest in the world (annual output exceeds 1.5×105t), and the subdivision categories are complete. Although my country's polylactic acid industry started late, it has developed rapidly. The scale of the industry currently under construction and expansion for the production of polymer-grade lactic acid and polylactic acid continues to grow. PLA fiber, as a biomass synthetic fiber derived from corn, cassava and agricultural waste, has good comfort, breathability and UV resistance, and has great development prospects in the field of new textile materials. However, the low melting point, poor thermal stability and low crystallinity of PLA fiber have seriously restricted the development of PLA fiber and hindered its application in the field of environmentally friendly fibers and textiles and clothing.

[0004] Chemical recycling is one of the key methods to solve the recycling of PLA-based materials. Waste PLA materials are depolymerized and converted into lactic acid, lactide and value-added lactate, which can be used as new raw materials for PLA synthesis to achieve repeated recycling. However, since exogenous additives are often required in the reuse of PLA materials, and these additives are difficult to separate during the PLA depolymerization process, they have a serious negative impact on the PLA decomposition products. Therefore, the development of bio-based materials that can be used to modify PLA and will not affect the decomposition of PLA is of great significance to the chemical recycling of PLA-based materials. Summary of the invention

[0005] Based on the above background, the present invention aims at the deficiencies in the prior art and provides a PLLA fiber that can be chemically recycled and has a high degree of crystallinity and a preparation method thereof. Bio-based nacre calcium carbonate is used to compound with PLLA masterbatch, and the entanglement between nacre calcium carbonate and PLLA molecular chains is enhanced and the nucleation sites of PLLA are increased by regulating the morphology, size and surface physicochemical structure of nacre calcium carbonate, thereby improving the melt strength of PLLA, promoting crystallinity and improving thermal stability, and achieving a high-crystallinity PLLA fiber with excellent mechanical strength and thermal stability.

[0006] The present invention adopts the following technical solutions:

[0007] A PLLA fiber that can be chemically recycled and has high crystallinity and a preparation method thereof, comprising the following steps:

[0008] (1) Separation and modification of bio-based nacre calcium carbonate from blue mussels: After cleaning, removing impurities, washing and drying the blue mussel shells, the shells are placed in an oven at a certain temperature for a certain period of time for heat treatment, and the nacre calcium carbonate in the treated blue mussel shells is separated to obtain crude nacre calcium carbonate. The crude nacre calcium carbonate is added to a dispersant, and after ultrasonic dispersion, crushing, modification and drying, submicron-level bio-based nacre calcium carbonate is obtained;

[0009] (2) Preparation of high-crystallinity PLLA fiber: Bio-based nacre calcium carbonate and PLLA masterbatch are added into an internal mixer in a certain proportion and mixed thoroughly, and granulated by a screw extruder to obtain a modified PLLA composite masterbatch. The composite masterbatch is extruded, stretched, and heat-treated by a melt spinning machine to obtain high-crystallinity PLLA fiber.

[0010] Based on the total dry weight of the raw materials being 100%, the content of the nacre calcium carbonate in the raw materials is 1-7%, and the content of the PLLA masterbatch in the raw materials is 93-99%.

[0011] In the step (1), the heat treatment temperature of the blue mussel shell is 220-300° C., and the treatment time is 2-6 hours;

[0012] Furthermore, the dispersant used in the crude nacre calcium carbonate is a mixed solvent composed of an organic acid and deionized water, wherein the organic acid is any one or a combination of acetic acid, citric acid, salicylic acid, oxalic acid, malic acid, tartaric acid, and benzoic acid;

[0013] The volume ratio of the organic acid to deionized water is 1:9-3:7.

[0014] Furthermore, the modifier used in the modification process of nacreous calcium carbonate is any one of KH550, KH792, Y5669, and Si-902, or a combination of several of them.

[0015] In the step (2), the processing temperature of the bio-based nacre calcium carbonate and the PLLA masterbatch in the internal mixer is 185-225° C., and the internal mixing time is 30-60 min.

[0016] Furthermore, when the pearl calcium carbonate and PLLA masterbatch mixed in the internal mixer are extruded and granulated by a screw, they are heated in four stages: the first stage heating temperature is 130-150°C; the second stage heating temperature is 160-180°C; the third stage heating temperature is 185-195°C; and the fourth stage heating temperature is 200-210°C.

[0017] Furthermore, the composite masterbatch needs to be vacuum dried for 4-8 hours before being extruded through a melt spinning machine, and the humidity in the workshop is strictly controlled to be no higher than 20% during the spinning process.

[0018] Furthermore, during the melt spinning process of the composite masterbatch, the temperature of the melt spinning machine cavity is 200-220° C., the spinning speed is 3000-6000 m / min, and the spinning pressure is 25-40 MPa.

[0019] Furthermore, the drawing rate of the PLLA fiber is 400-600 m / min, and the drawing temperature is 200-220°C.

[0020] The present invention has the following beneficial effects:

[0021] (1) The use of nacre calcium carbonate from bio-based blue mussel shells as a reinforcing material not only achieves the effective utilization of waste biomass shell resources, increases their added value, and realizes the effective utilization of becquerel biomass materials, but also the composite of biomass materials and PLLA does not affect its inherent biodegradability, which is an environmentally friendly preparation scheme;

[0022] (2) The present invention effectively regulates the physical morphology and chemical structure of bio-based nacre calcium carbonate during its preparation process, and solves the problem of interface incompatibility between inorganic material calcium carbonate and polymer PLLA during the composite process by controlling the ultrasonic crushing time and surface functional groups, while improving the uniformity of the two after mixing;

[0023] (3) The high-crystallinity PLLA fiber prepared by the present invention is carried out by melt spinning. By regulating the external and internal related parameters during the spinning process, the continuous spinning of the high-crystallinity PLLA fiber is achieved. Compared with the solution spinning and solvent-assisted spinning technologies, this technology is more environmentally friendly;

[0024] (4) In the preparation method of the present invention, the PLLA fiber undergoes subsequent stretching and heat treatment, and the polymer molecular chains can be effectively oriented and increase the internal entanglement with calcium carbonate during the post-treatment process to form a more ordered structure, thereby improving the crystallinity and mechanical strength of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the bio-based nacre calcium carbonate of the present invention;

[0026] Figure 2 This is the surface SEM image of PLLA fiber prepared without composite nacreous calcium carbonate;

[0027] Figure 3 The surface SEM image of PLLA fiber prepared by compounding 7% nacreous calcium carbonate;

[0028] Figure 4 This is the SEM image of the cross section of PLLA fiber prepared by compounding 5% nacreous calcium carbonate;

[0029] Figure 5 DSC heating curves of PLLA fibers with different nacreous calcium carbonate composite ratios (heating rate 5℃ / min) 。 DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0031] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0032] A PLLA fiber that can be chemically recycled and has high crystallinity and a preparation method thereof are prepared by composite granulation of modified nacre calcium carbonate and PLLA and melt spinning:

[0033] (1) Separation and modification of bio-based nacre calcium carbonate from blue mussels: After cleaning, removing impurities, washing and drying the blue mussel shells, the shells are placed in an oven at a certain temperature for a certain period of time for heat treatment, and the nacre calcium carbonate in the treated blue mussel shells is separated to obtain crude nacre calcium carbonate. The crude nacre calcium carbonate is added to a dispersant, and after ultrasonic dispersion, crushing, modification and drying, submicron-level bio-based nacre calcium carbonate is obtained;

[0034] The heat treatment temperature of the blue mussel shell is 220-300° C., and the treatment time is 2-6 hours;

[0035] Specifically, the dispersant used in the crude nacre calcium carbonate is a mixed solvent composed of an organic acid and deionized water, and the organic acid is any one or a combination of acetic acid, citric acid, salicylic acid, oxalic acid, malic acid, tartaric acid, and benzoic acid;

[0036] The volume ratio of the organic acid to deionized water is 1:9-3:7.

[0037] The modifier used in the modification process of nacre calcium carbonate is any one of KH550, KH792, Y5669 and Si-902 or a combination of several of them.

[0038] (2) Preparation of high-crystallinity PLLA fiber: Bio-based nacre calcium carbonate and PLLA masterbatch are added into an internal mixer in a certain proportion and mixed thoroughly, and granulated by a screw extruder to obtain a modified PLLA composite masterbatch. The composite masterbatch is extruded, stretched, and heat-treated by a melt spinning machine to obtain high-crystallinity PLLA fiber.

[0039] Based on the total dry weight of the raw materials being 100%, the content of the nacre calcium carbonate in the raw materials is 1-7%, and the content of the PLLA masterbatch in the raw materials is 93-99%.

[0040] Specifically, the processing temperature of the bio-based nacre calcium carbonate and PLLA masterbatch in the internal mixer is 185-225° C., and the internal mixing time is 30-60 min.

[0041] When the pearl calcium carbonate and PLLA masterbatch mixed in the internal mixer are extruded and granulated by a screw, they are heated in four stages: the first stage heating temperature is 130-150°C; the second stage heating temperature is 160-180°C; the third stage heating temperature is 185-195°C; and the fourth stage heating temperature is 200-210°C.

[0042] The composite masterbatch needs to be vacuum dried for 4-8 hours before being extruded through the melt spinning machine. At the same time, the workshop humidity is strictly controlled not to exceed 20% during the spinning process.

[0043] Specifically, during the melt spinning process of the composite masterbatch, the temperature of the melt spinning machine cavity is 200-220° C., the spinning speed is 3000-6000 m / min, and the spinning pressure is 25-40 MPa.

[0044] The drawing rate of the PLLA fiber is 400-600 m / min, and the drawing temperature is 200-220°C.

[0045] Example 1

[0046] The blue mussel shells are cleaned, impurity-removed, washed and dried, and then placed in a 220° C. forced air oven for heat treatment for 6 hours to separate the nacre calcium carbonate in the treated blue mussel shells to obtain crude nacre calcium carbonate.

[0047] The crude nacre calcium carbonate is added into a dispersion solvent having a volume ratio of 1:9 of acetic acid and deionized water, and the mixture of the nacre calcium carbonate and the dispersion solvent is ultrasonically dispersed in an ultrasonicator at 60°C for 2 hours, and then further crushed by a cell crusher for 30 minutes. The further crushed nacre calcium carbonate is filtered, washed with water, and dried to obtain unmodified submicron nacre calcium carbonate.

[0048] Surface modification of submicron nacre calcium carbonate: KH550 and anhydrous ethanol were added to a 1000 ml beaker at a volume ratio of 1:10, stirred for 30 minutes to fully mix, and then 500 g of submicron nacre calcium carbonate was added to the mixed solution for reaction. During the reaction, in order to ensure that the reaction was fully carried out, the beaker was placed in a constant temperature water bath at 40°C and stirred for 4 hours. After the reaction, the nacre calcium carbonate was filtered, washed with alcohol, and dried to obtain modified nacre calcium carbonate.

[0049] Bio-based nacre calcium carbonate and PLLA masterbatch were added to an internal mixer at a mass ratio of 1:99 and fully mixed. The processing temperature of nacre calcium carbonate and PLLA masterbatch in the internal mixer was 185°C and the internal mixing time was 60 minutes. The nacre calcium carbonate and PLLA masterbatch mixed in the internal mixer were extruded and granulated by a screw, and heated in four stages: the first stage heating temperature was 130°C; the second stage heating temperature was 160°C; the third stage heating temperature was 185°C; and the fourth stage heating temperature was 200°C to obtain PLLA composite masterbatch.

[0050] The composite masterbatch was vacuum dried for 4 hours and then added into a melt spinning machine. During the melt spinning process, the cavity temperature of the melt spinning machine was set to 200°C, the spinning speed was set to 3000m / min, the spinning pressure was set to 25Mpa, the drawing rate was set to 400m / min, and the drawing temperature was set to 200°C to prepare highly crystalline PLLA fibers.

[0051] The microscopic morphology of the modified nacre calcium carbonate described in this embodiment is as follows: Figure 1 As shown, the DSC temperature rise curve of the high crystalline PLLA fiber is as follows Figure 5 The crystallinity of PLLA fibers is shown in Table 1. Figure 1 It can be seen that the nacre calcium carbonate has a lamellar structure, and the lamellar width is in the submicron range (100nm-1000nm). Figure 5 The DSC temperature rise curve of 1%-nacre / PLLA shows that the fiber has a cold crystallization peak at about 99.24°C, and the crystal structure inside the surface fiber has changed. As can be seen from Table 1, the crystallinity of 1%-nacre / PLLA can reach 64.46%.

[0052] Example 2

[0053] The blue mussel shells are cleaned, impurity-removed, washed and dried, and then placed in a 250° C. forced air oven for heat treatment for 4 hours to separate the nacre calcium carbonate in the treated blue mussel shells to obtain crude nacre calcium carbonate.

[0054] The crude nacre calcium carbonate is added to a dispersion solvent of oxalic acid and deionized water in a volume ratio of 3:7, the mixture of nacre calcium carbonate and dispersion solvent is placed in a 60°C ultrasonicator for ultrasonic dispersion for 2 hours, and then further crushed by a cell crusher for 30 minutes. The further crushed nacre calcium carbonate is filtered, washed with water, and dried to obtain unmodified submicron nacre calcium carbonate.

[0055] Surface modification of submicron nacre calcium carbonate: Y5669 and anhydrous ethanol were added to a 1000 ml beaker at a volume ratio of 1:10, stirred for 30 minutes to fully mix, and then 500 g of submicron nacre calcium carbonate was added to the mixed solution for reaction. During the reaction, in order to ensure that the reaction was fully carried out, the beaker was placed in a constant temperature water bath at 40°C and stirred for 4 hours. After the reaction, the nacre calcium carbonate was filtered, washed with alcohol, and dried to obtain modified nacre calcium carbonate.

[0056] Bio-based nacre calcium carbonate and PLLA masterbatch were added to the internal mixer at a mass ratio of 3:97 and fully mixed. The processing temperature of nacre calcium carbonate and PLLA masterbatch in the internal mixer was 210°C and the internal mixing time was 40 minutes. The nacre calcium carbonate and PLLA masterbatch mixed in the internal mixer were extruded by a screw and granulated, and heated in four stages: the first stage heating temperature was 135°C; the second stage heating temperature was 165°C; the third stage heating temperature was 185°C; and the fourth stage heating temperature was 205°C to obtain the PLLA composite masterbatch.

[0057] The composite masterbatch was vacuum dried for 4 hours and then added to the melt spinning machine. The melt spinning machine cavity temperature was set to 205°C, the spinning speed was 3500m / min, the spinning pressure was 30Mpa, the drawing rate was 450m / min, and the drawing temperature was 205°C during the melt spinning process to prepare highly crystalline PLLA fibers.

[0058] The DSC temperature rise curve of the high crystalline PLLA fiber in this embodiment is as follows: Figure 5 The crystallinity of the 3%-nacre / PLLA fiber is shown in Table 1. Figure 5 The DSC temperature rise curve of 3%-pearl / PLLA shows that the fiber has a cold crystallization peak at about 97.83°C, and the crystal structure inside the surface fiber has changed. As can be seen from Table 1, the crystallinity of 3%-pearl / PLLA can reach 68.90%.

[0059] Example 3

[0060] The blue mussel shells were cleaned, cleaned, washed and dried, and then placed in a 230° C. forced air oven for heat treatment for 5 hours to separate the nacre calcium carbonate in the treated blue mussel shells to obtain crude nacre calcium carbonate.

[0061] The crude nacre calcium carbonate is added to a dispersion solvent of salicylic acid and deionized water in a volume ratio of 2:8, the mixture of the nacre calcium carbonate and the dispersion solvent is ultrasonically dispersed in an ultrasonicator at 60°C for 2 hours, and then further crushed by a cell crusher for 30 minutes. The further crushed nacre calcium carbonate is filtered, washed with water, and dried to obtain unmodified submicron nacre calcium carbonate.

[0062] Surface modification of submicron nacre calcium carbonate: KH792 and anhydrous ethanol were added to a 1000 ml beaker at a volume ratio of 1:10, stirred for 30 minutes to fully mix, and then 500 g of submicron nacre calcium carbonate was added to the mixed solution for reaction. During the reaction, in order to ensure that the reaction was fully carried out, the beaker was placed in a constant temperature water bath at 40°C and stirred for 4 hours. After the reaction, the nacre calcium carbonate was filtered, washed with alcohol, and dried to obtain modified nacre calcium carbonate.

[0063] Bio-based nacre calcium carbonate and PLLA masterbatch were added to the internal mixer at a mass ratio of 5:95 and fully mixed. The processing temperature of nacre calcium carbonate and PLLA masterbatch in the internal mixer was 195°C and the internal mixing time was 50 minutes. The nacre calcium carbonate and PLLA masterbatch mixed in the internal mixer were extruded by a screw and granulated, and heated in four stages: the first stage heating temperature was 140°C; the second stage heating temperature was 170°C; the third stage heating temperature was 190°C; and the fourth stage heating temperature was 205°C to obtain PLLA composite masterbatch.

[0064] The composite masterbatch was vacuum dried for 6 hours and then added to a melt spinning machine. The melt spinning machine cavity temperature was set to 210°C, the spinning speed was 4000m / min, the spinning pressure was 35Mpa, the drawing rate was 500m / min, and the drawing temperature was 210°C during the melt spinning process to prepare highly crystalline PLLA fibers.

[0065] The cross-sectional microstructure of the highly crystalline PLLA fiber described in this embodiment is as follows: Figure 4 The fiber DSC heating curve is shown in the cross-section SEM. Figure 5 The crystallinity of the 5%-nacre / PLLA fiber is shown in Table 1. Figure 4 It can be seen that the modified nacreous calcium carbonate is evenly coated in the PLLA fiber, and the two have good bonding and no interface incompatibility problem occurs. Figure 5 The DSC temperature rise curve of 5%-pearl / PLLA shows that the fiber has a cold crystallization peak at about 97.70℃, and the crystal structure inside the surface fiber has changed. As can be seen from Table 1, the crystallinity of 5%-pearl / PLLA can reach 72.31%.

[0066] Example 4

[0067] The blue mussel shells are cleaned, cleaned, washed and dried, and then placed in a 300° C. forced air oven for heat treatment for 2 hours to separate the nacre calcium carbonate in the treated blue mussel shells to obtain crude nacre calcium carbonate.

[0068] The crude nacre calcium carbonate is added to a dispersion solvent of benzoic acid and deionized water in a volume ratio of 3:7, the mixture of nacre calcium carbonate and dispersion solvent is placed in a 60°C ultrasonicator for ultrasonic dispersion for 2 hours, and then further crushed by a cell crusher for 30 minutes. The further crushed nacre calcium carbonate is filtered, washed with water, and dried to obtain unmodified submicron nacre calcium carbonate.

[0069] Surface modification of submicron nacre calcium carbonate: Si-902 and anhydrous ethanol were added to a 1000 ml beaker at a volume ratio of 1:10, stirred for 30 minutes to fully mix, and then 500 g of submicron nacre calcium carbonate was added to the mixed solution for reaction. During the reaction, in order to ensure that the reaction was fully carried out, the beaker was placed in a constant temperature water bath at 40°C and stirred for 4 hours. After the reaction, the nacre calcium carbonate was filtered, washed with alcohol, and dried to obtain modified nacre calcium carbonate.

[0070] Bio-based nacre calcium carbonate and PLLA masterbatch were added to the internal mixer at a mass ratio of 7:93 and fully mixed. The processing temperature of nacre calcium carbonate and PLLA masterbatch in the internal mixer was 225°C and the internal mixing time was 30 minutes. The nacre calcium carbonate and PLLA masterbatch mixed in the internal mixer were extruded by a screw and granulated, and heated in four stages: the first stage heating temperature was 150°C; the second stage heating temperature was 180°C; the third stage heating temperature was 195°C; the fourth stage heating temperature was 210°C, and the PLLA composite masterbatch was obtained.

[0071] The composite masterbatch was vacuum dried for 8 hours and then added to a melt spinning machine. The melt spinning machine cavity temperature was set to 220°C, the spinning speed was 6000m / min, the spinning pressure was 40Mpa, the drawing rate was 600m / min, and the drawing temperature was 220°C during the melt spinning process to prepare highly crystalline PLLA fibers.

[0072] The surface microstructure of the highly crystalline PLLA fiber described in this embodiment is as follows Figure 3 As shown in the SEM picture, the fiber DSC heating curve is as follows Figure 5 The crystallinity of the 7%-nacre / PLLA fiber is shown in Table 1. Figure 3 It can be seen that the modified nacreous calcium carbonate is evenly dispersed on the surface of PLLA fiber. Figure 5 The DSC temperature rise curve of 7%-pearl / PLLA shows that the fiber has a cold crystallization peak at about 98.04°C, and the crystal structure inside the surface fiber has changed. As can be seen from Table 1, the crystallinity of 7%-pearl / PLLA can reach 79.16%.

[0073] Comparative Example 1

[0074] The PLLA fiber was prepared by the method of Example 4, except that the PLLA was directly spun without being modified with nacreous calcium carbonate.

[0075] The surface morphology of the PLLA fiber prepared in this comparative example is as follows: Figure 2 As shown in the SEM picture, the fiber DSC heating curve is as follows Figure 5The crystallinity of the PLLA fibers is shown in Table 1. Figure 2 The SEM image shows that the surface of the unmodified PLLA fiber is smooth. Figure 5 The DSC temperature rise curve of PLLA shows that the fiber has no cold crystallization peak. As can be seen from Table 1, the crystallinity of PLLA is only 36.76%.

[0076] Table 1 shows the crystallinity of PLLA fibers with different nacreous calcium carbonate composite ratios

[0077]

[0078] The technical features of the above-described embodiments may be combined arbitrarily. A person skilled in the art may make several modifications and improvements without departing from the concept of the present invention. These modifications and improvements all belong to the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A PLLA fiber that can be chemically recycled and has high crystallinity and a preparation method thereof, characterized in that: The following steps are involved: (1) Separation and modification of bio-based nacre calcium carbonate from blue mussels: After cleaning, removing impurities, washing and drying the blue mussel shells, the shells are placed in an oven at a certain temperature for a certain period of time for heat treatment, and the nacre calcium carbonate in the treated blue mussel shells is separated to obtain crude nacre calcium carbonate. The crude nacre calcium carbonate is added to a dispersant, and after ultrasonic dispersion, crushing, modification and drying, submicron-level bio-based nacre calcium carbonate is obtained; (2) Preparation of high-crystallinity PLLA fiber: Bio-based nacre calcium carbonate and PLLA masterbatch are added into an internal mixer in a certain proportion and mixed thoroughly, and granulated by a screw extruder to obtain a modified PLLA composite masterbatch. The composite masterbatch is extruded, stretched, and heat-treated by a melt spinning machine to obtain high-crystallinity PLLA fiber. Based on the total dry weight of the raw materials being 100%, the content of the nacre calcium carbonate in the raw materials is 1-7%, and the content of the PLLA masterbatch in the raw materials is 93-99%.

2. The PLLA fiber with high crystallinity and chemical recyclability according to claim 1, characterized in that: In step (1), the heat treatment temperature of the blue mussel shell is 220-300° C., and the treatment time is 2-6 hours.

3. The PLLA fiber with high crystallinity and chemical recyclability according to claim 1, characterized in that: In step (1), the dispersant used for the crude nacre calcium carbonate is a mixed solvent consisting of an organic acid and deionized water, wherein the organic acid is any one or a combination of acetic acid, citric acid, salicylic acid, oxalic acid, malic acid, tartaric acid, and benzoic acid; The volume ratio of the organic acid to deionized water is 1:9-3:

7.

4. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (1), the modifier used in the modification process of nacreous calcium carbonate is any one of KH550, KH792, Y5669, and Si-902, or a combination of several of them.

5. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (2), the processing temperature of the bio-based nacre calcium carbonate and the PLLA masterbatch in the internal mixer is 185-225° C., and the internal mixing time is 30-60 min.

6. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (2), when the pearl calcium carbonate and PLLA masterbatch mixed in the internal mixer are extruded and granulated by a screw, they are heated in four stages: the first stage heating temperature is 130-150°C; the second stage heating temperature is 160-180°C; the third stage heating temperature is 185-195°C; and the fourth stage heating temperature is 200-210°C.

7. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (2), the composite masterbatch needs to be vacuum dried for 4-8 hours before being extruded through a melt spinning machine, and the workshop humidity is strictly controlled to be no higher than 20% during the spinning process.

8. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (2), during the melt spinning process of the composite masterbatch, the temperature of the melt spinning machine cavity is 200-220°C, the spinning speed is 3000-6000m / min, and the spinning pressure is 25-40Mpa.

9. The chemically recyclable PLLA fiber with high crystallinity and the preparation method thereof according to claim 1, characterized in that: In step (2), the drawing rate of the PLLA fiber is 400-600 m / min, and the drawing temperature is 200-220°C.

Citation Information

Patent Citations

  • Method for preparing functional calcium carbonate by using mussel shells as raw material

    CN101920982A

  • Preparation method of modified shell powder with good dispersibility

    CN108822579A

  • Shell powder modified polylactic acid composite material, preparation method and applications thereof

    CN110591316A

  • Full-degradable high-crystallinity low-water-absorption polylactic acid fiber and preparation method thereof

    CN112626637A

  • Shell biological calcium / polylactic acid composite material with antibacterial function as well as preparation method and application of shell biological calcium / polylactic acid composite material

    CN115558259A